Exploring recovery capital among adolescents in an alternative peer group. (1st June 2019) - Nash, Angela J.; Hennessy, Emily A.; Collier, Crystal
Highlights: Recovery capital (RC) is the internal and external resources needed to sustain recovery. The RCAM is a framework for understanding adolescent recovery processes. The Alternative Peer Group (APG) aims to build RC in adolescents. The RCAM is useful for identifying recovery assets and barriers adolescents face. Potential pathways of RC resource-building in an APG are presented. Abstract: Background: Recovery support models (RSMs) integrate peer supports and continuing care to promote sustained recovery for adolescents with substance use disorder. RSMs aim to build recovery capital (RC), the personal, social, and environmental resources required to sustain recovery. The Alternative Peer Group (APG) is an RSM that integrates pro-recovery peers and social activities into clinical practice. APGs aim to build adolescents' RC and help them establish pro-recovery social networks. The Recovery Capital for Adolescents Model (RCAM) is a proposed framework for identifying assets to enhance and barriers to address in supporting adolescents' recovery. The RCAM has never been directly applied in APG research so little is known about the process of building RC while participating in an APG. Methods: This study is a secondary analysis of semi-structured interviews with APG participants. Using a deductive analytic approach, the RCAM was systematically applied to participants' narratives to examine the model's utility for identifying recovery barriers and resources that promote adolescent recovery. Findings: This study's findings confirmed the RCAM's utility for identifying specific recovery assets and barriers to recovery faced by adolescents. APG participants' narratives generally reflected the RCAMs RC domains (financial, human, social and community) as proposed and added details to refine the model. Specific strategies employed by the APG to enhance RC and address recovery barriers are presented and illustrated with qualitative exemplars. Conclusions: The RCAM is a useful model for identifying the multiple, interrelated factors inherent to adolescents' recovery experience and potential pathways of RC resource-building.